2021
DOI: 10.1136/bmjdrc-2020-002016
|View full text |Cite
|
Sign up to set email alerts
|

Serum calcification propensity is associated with HbA1c in type 2 diabetes mellitus

Abstract: IntroductionSerum calcification propensity is emerging as an independent predictor for cardiovascular outcomes in high-risk populations. Calcification propensity can be monitored by the maturation time of calciprotein particles in serum (T50 test). A low T50 value is an independent determinant of cardiovascular morbidity and mortality in various populations. Aim was to investigate the T50 and its relationship to type 2 diabetes mellitus.Research design and methodsUsing nephelometry, serum T50 was cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
3
12
1
Order By: Relevance
“…Findings from large populationbased cohorts identified a VC prevalence of 40% to 60% and 30% to 40% among older [1,2] and middle-aged adults [3]. Meta-analyses revealed that the VC prevalence rose to 60% among patients with CKD regardless of age [4] and also increased in those with DM [5]. Calcifications affecting conduit arteries lead to vessel stiffening, increased peripheral resistance and the risk of hypertension, cardiac hypertrophy, heart failure and cardiovascular mortality.…”
Section: Vascular Calcification (Vc): An Introductionmentioning
confidence: 99%
“…Findings from large populationbased cohorts identified a VC prevalence of 40% to 60% and 30% to 40% among older [1,2] and middle-aged adults [3]. Meta-analyses revealed that the VC prevalence rose to 60% among patients with CKD regardless of age [4] and also increased in those with DM [5]. Calcifications affecting conduit arteries lead to vessel stiffening, increased peripheral resistance and the risk of hypertension, cardiac hypertrophy, heart failure and cardiovascular mortality.…”
Section: Vascular Calcification (Vc): An Introductionmentioning
confidence: 99%
“…The T 50 test depends on calcification promoters and inhibitors present in the serum and is associated with cardiovascular mortality ( 23 ). Several studies have indicated that T 50 -values decrease in chronic renal failure or diabetes ( 23 , 32 ). T 50 -values of patients on dialysis are lower than in pre-dialysis patient, and associate with clinical outcomes ( 24 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Across many studies, plasma phosphate was consistently the strongest determinant of serum T50, even after multivariable adjustment [ 131 , 132 ]. Recently we performed a study in 932 patients with type 2 diabetes and discovered that glycosylated hemoglobin (HbA1c), reflecting long-term glycemic control, was inversely associated with serum T50 levels upon multivariate analysis [ 133 ]. Low serum T50 levels have also been associated with markers of inflammatory stress (such as TNF-α), as well as with markers of bone resorption [ 131 ].…”
Section: Consequences Of Phosphate Deregulations In Diabetesmentioning
confidence: 99%